Understanding Procrastination: Role of Time Management and Task Aversiveness in Shaping Mathematics Achievement - Sharma Chapai, Krishna Prasad; Joshi, Dirgha Raj (KMC Journal, 2025)
Academic procrastination is the deliberate delay of academic tasks, which is frequently caused by various reasons such as poor time management, disinterest in task or lack of motivation, sincerity, perfectionism or external socio-demographic variables. These behaviors can adversely affect students’ academic performance. The present study aims to examine the status of students’ time management and task aversiveness in academic procrastination. This study further investigates their role in shaping mathematics achievement. A quantitative research approach with a cross-sectional survey research design was used among 474 secondary level students of Bardiya district. The data were analyzed by using t-tests, ANOVA and multiple linear regressions. The finding reveals that time management and task aversiveness are significant contributors to procrastination. Additionally, regression analysis shows that study hour, aversiveness of task, ethnicity, father education and mother education are major significant factors to determine mathematics achievement score. These results underscore the critical need for collaborative efforts among parents, teachers and policymakers to address the root causes of procrastination and enhance students’ academic performance. Developing targeted interventions and support systems can foster better time management and reduce task aversiveness, ultimately leading to improved learning outcomes in mathematics and beyond.